2021
DOI: 10.1016/j.neubiorev.2021.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting effects of prenatal stress on HPA axis and inflammation: A systematic review and multilevel meta-analysis in rodent studies

Abstract: Exposure to prenatal stress (PNS) can lead to long-lasting neurobiological and behavioral consequences for the offspring, which may enhance the susceptibility for mental disorders. The hypothalamus-pituitaryadrenal (HPA) axis and the immune system are two major factors involved in the stress response. Here, we performed a systematic review and metaanalysis of rodent studies that investigated the effects of PNS exposure on the HPA axis and inflammatory cytokines in adult offspring. Our analysis shows that anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…Several animal experiments assessed effects of acute social isolation on the HPA axis. In mice and rats, a systematic review and meta-analysis suggested that prenatal stress (e.g., due to hypoxia or s.c. dexamethasone injection in the pregnant animal) results in a significant increase in peripheral cortisol concentrations in adult offspring, who also showed increased corticotrophin-releasing hormone levels, particularly in males, and decreased levels of its corticotrophin-releasing hormone receptor 2 [ 31 ]. Separating new-born rodents from their mothers and rearing them in social isolation also increases HPA axis activity.…”
Section: Animal Models Of Social Isolation Distressmentioning
confidence: 99%
“…Several animal experiments assessed effects of acute social isolation on the HPA axis. In mice and rats, a systematic review and meta-analysis suggested that prenatal stress (e.g., due to hypoxia or s.c. dexamethasone injection in the pregnant animal) results in a significant increase in peripheral cortisol concentrations in adult offspring, who also showed increased corticotrophin-releasing hormone levels, particularly in males, and decreased levels of its corticotrophin-releasing hormone receptor 2 [ 31 ]. Separating new-born rodents from their mothers and rearing them in social isolation also increases HPA axis activity.…”
Section: Animal Models Of Social Isolation Distressmentioning
confidence: 99%
“…The limitations of human memory specifically precluded participants in our study from reporting adversity that occurred either in utero or during the early postnatal period. This is relevant given that prenatal and early postnatal stress has effects on the brain and immune system ( Creutzberg et al., 2021 ; Dutcher et al., 2020 ; Weinstock, 2016 ). An additional limitation includes focus on cross-sectional effects in three menopause stages due to limited availability of leftover blood samples for cytokine measurement.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that three broad strategies were used when non-independence was encountered in animal meta-analyses (Figure 5): (1) ignoring non-independence (Lages et al, 2021;Mancini et al, 2020), (2) eliminating non-independence (e.g., averaging or sampling; Currie et al, 2019;Frantzias et al, 2011), and (3) modelling dependence explicitly (Bonapersona et al, 2018;Creutzberg et al, 2021). The first approach was the most used method employed in animal meta-analyses (48%; Figure 3), which is concerning as it ignores the dependency among effect sizes and treats them as if they were statistically independent (i.e., via the use of simple fixed-and J o u r n a l P r e -p r o o f random-effects models for analysing non-independent effect sizes).…”
Section: Approaches To Handle Statistical Non-independence In the Met...mentioning
confidence: 99%